Bibliometric analysis of global research profile on ketogenic diet therapies in neurological diseases: Beneficial diet therapies deserve more attention - Wang, Yinuo; Zhang, Junyao; Zhang, Yingying; Yao, Junyan (Frontiers in Endocrinology, 2023)
Background: The protective effects of Ketogenic Diet Therapies (KDTs) on neurological diseases have been extensively studied over the past two decades. The purpose of this study was to quantitatively and qualitatively analyze the publication of KDTs in the neurological field from 2000 to 2021. Methods: A literature search was performed on June 7th, 2022, using the search terms: ((“ketone” OR “ketogenic” OR “*hydroxybuty*”) AND (“neuro*”)) in the WoSCC database. Collected data were further analyzed using VOSviewer, CiteSpace and other online bibliometric websites. The annual publication volume and citation trends were summarized. The collaborations among highly cited countries, institutions, authors and journals were visualized. The co-citation analysis of highly cited references and journals were also visualized. Moreover, the research focuses and fronts were revealed by co-occurrence analysis and burst keywords detection. Results: A total of 2808 publications with 88,119 citations were identified. From 2000-2021, the number of publications and citations presented rising trends. The United States was the country with an overwhelming number of publications and cited times. Johns Hopkins University was the most contributory institution. Kossoff Eric H was the author with the largest number of publications. And Epilepsia was both the largest publisher and the most frequently cited journal. The keywords of intense interest involved “Modified Atkins Diet”, “Temporal Lobe Epilepsy”, “Alzheimer’s Disease”, “Parkinson’s Disease”, “Cerebral Blood Flow”, “Neuroinflammation”, “Oxidative Stress”, “Metabolism” and “Mitochondria”. Conclusion: We presented the global trend of KDTs in neurological diseases and provided important information for relevant researchers in a bibliometric way. This bibliometric study revealed that treating epilepsy, neuroprotection and functional effects of KDTs on mitochondria and oxidative stress have been the spotlight from 2000 to 2021. These have emerged as the basis for transformation from basic research to clinical application of KDTs.